Campaign 9 of the K2 mission: observational parameters, scientific drivers, and community Involvement for a simultaneous space- and ground-based microlensing survey - Henderson, Calen B.; Schmidt, Robert W.; Tsapras, Yiannis; Wambsganß, Joachim (Publications of the Astronomical Society of the Pacific, 2016)
K2 's Campaign 9 ( K2 C9) will conduct a ∼3.7 deg 2 survey toward the Galactic bulge from 2016 April 22 through July 2 that will leverage the spatial separation between K2 and the Earth to facilitate measurement of the microlens parallax ##IMG## [http://ej.iop.org/images/1538-3873/128/970/124401/paspaa340eieqn1.gif] $π _\rmE$ for ##IMG## [http://ej.iop.org/images/1538-3873/128/970/124401/paspaa340eieqn2.gif] $\gtrsim 170$ microlensing events. These will include several that are planetary in nature as well as many short-timescale microlensing events, which are potentially indicative of free-floating planets (FFPs). These satellite parallax measurements will in turn allow for the direct measurement of the masses of and distances to the lensing systems. In this article we provide an overview of the K2 C9 space- and ground-based microlensing survey. Specifically, we detail the demographic questions that can be addressed by this program, including the frequency of FFPs and the Galactic distribution of exoplanets, the observational parameters of K2 C9, and the array of resources dedicated to concurrent observations. Finally, we outline the avenues through which the larger community can become involved, and generally encourage participation in K2 C9, which constitutes an important pathfinding mission and community exercise in anticipation of WFIRST .